PENGARUH KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA AUDITOR PEMERINTAH DENGAN KEPEMIMPINAN DAN JABATAN SEBAGAI VARIABEL INTERVENING - Yuniarto, Arif Sapta (PERMANA, 2013)
The main object of this research is to make empirically analisys the impact leadership and organizational position toward job satisfaction, and include organizational comitment as intervening variable. The result of research is expected to give contribution due to developing the theory, especially concerned within attitude accountancy. In addition, expected to give practical contribution for organizational especially BPKP Yogyakarta office. This research have taken goverment auditor as an object in BPKP office, used stratified sampling method by questioner dissemination. Path analisys tool is used to response submitted problem formulation. Based on the result of research can see that submitted four hyphotesis of the research are rejected. The result indicated that there is significant direct effect between leadership and organizational position toward job satisfaction goverment auditor in BPKP Yogyakarta office. Variable of organizational comitment have unsignificantly influence to job satisfaction. Key words: organizational comitment, job satisfaction, leadership and organizational position.